Evaluation of AGA and Fukuoka Guidelines for EUS and surgical resection of incidental pancreatic cysts - Alexander Lee; Vivek Kadiyala; Linda S. Lee (Endoscopy International Open, 2017)
Objectives Management of asymptomatic pancreatic cysts is challenging. Guidelines by the American Gastroenterological Association (AGA) and International Association of Pancreatology (Fukuoka) seek to identify high-risk patients. We assessed performance of these guidelines in selecting patients for endoscopic ultrasound (EUS) and/or surgery. Methods PART I – We retrospectively studied 143 asymptomatic cysts with magnetic resonance imaging (MRI) followed by EUS. Appropriate selection for EUS was defined as: malignant cytology or surgical pathology, or development of concerning features on MRI as defined by the guidelines. PART II – We retrospectively studied 152 resected cysts to assess the performance of guidelines in selecting cysts for surgery using malignant histology as the outcome. Results PART I – Of 143 EUS, 43 (30.1 %) were male with median age 65.0 years (interquartile range [IQR] 58.0 – 73.0). AGA guideline demonstrated lower sensitivity (17.6 % versus 35.3 %, P = 0.03), higher specificity (94.5 % versus 66.1 %, p < 0.001), and higher accuracy (76.2 % versus 58.7 %, P = 0.002) than Fukuoka. There was no difference in positive predictive value (50.0 % versus 24.5 %, P = 0.15) and negative predictive value (78.6 % versus 76.6 %, p=0.75). PART II – Of 152 resected cysts, 45 (29.8 %) were male with median age 59.0 years (IQR 47.3 – 66.7). There was no difference in performance characteristics of the guidelines in selecting cysts for surgery. AGA and Fukuoka guidelines missed 25.0 % and 18.8 % of malignant cysts, respectively (P = 1.00). Conclusions For referral to EUS, the AGA guideline was highly specific compared to Fukuoka; both suffered from poor sensitivity, although the Fukuoka guideline was relatively more sensitive than AGA. For referral to surgery, both guidelines have modest sensitivity and specificity and miss a similar percentage of malignant lesions.